TECHNOLOGY OF ONYCHOMYCOSIS PREVENTION - KACHAN, ROMAN (Herald of Khmelnytskyi National University. Technical sciences, 2024)
The work investigated the problem of preventing the occurrence of onychomycosis. The need to disinfect various materials of a person with mycosis: shoes, socks, clothes, surfaces, sanitary equipment and other materials that can be infected with pathogens of mycosis, in order to minimize re-infection and infection of family members, was substantiated. Currently, on the Ukrainian market of means for the prevention of mycosis, mainly disinfectants are used, which are toxic and have a negative effect on treated surfaces. Thus, there is an urgent need to create an effective, safe means for disinfecting shoes and other materials and surfaces that may be infected with onychomycosis pathogens. The tool should be universal, suitable for processing all surfaces and materials. A significant number of active substances belonging to cation-active surfactants have pronounced fungicidal properties, do not have a negative effect on materials and surfaces, and are safe for humans. Therefore, when creating a disinfectant against onychomycosis, a number of substances related to cationic active surfactants were studied. It was established that the most optimal active component of the new disinfectant is didecyldimethylammonium chloride. On the basis of this substance, a tool and technology for the prevention of onychomycosis was created. Also, nonionic surfactant - ethoxylated alcohol was added to the product. It enhances the fungicidal effect of the disinfectant and gives it a cleaning ability. This property is quite an important component of the disinfectant. First, dirt interferes with the effective action of the biocide, accordingly, the latter is inactivated. Secondly, if there is a small amount of dirt on clothes and shoes, after fungicidal treatment, it will be enough to rinse it with running water so that the clothes and shoes become clean.
Keywords: prevention of onychomycosis; disinfectant; socks; shoes; didecyldimethylammonium chloride